Boundary Layer of Photon Absorption Applied to Heterogeneous Photocatalytic Solar Flat Plate Reactor Design - Héctor L. Otálvaro-Marín; Miguel Angel Mueses; Fiderman Machuca-Martínez (International Journal of Photoenergy)
This study provides information to design heterogeneous photocatalytic solar reactors with flat plate geometry used in treatment of effluents and conversion of biomass to hydrogen. The concept of boundary layer of photon absorption taking into account the efficient absorption of radiant energy was introduced; this concept can be understood as the reactor thickness measured from the irradiated surface where 99% of total energy is absorbed. Its thickness and the volumetric rate of photons absorption (VRPA) were used as design parameters to determine (i) reactor thickness, (ii) maximum absorbed radiant energy, and (iii) the optimal catalyst concentration. Six different commercial brands of titanium dioxide were studied: Evonik-Degussa P-25, Aldrich, Merck, Hombikat, Fluka, and Fisher. The local volumetric rate of photon absorption (LVRPA) inside the reactor was described using six-flux absorption-scattering model (SFM) applied to solar radiation. The radiation field and the boundary layer thickness of photon absorption were simulated with absorption and dispersion effects of catalysts in water at different catalyst loadings. The relationship between catalyst loading and reactor thickness that maximizes the absorption of radiant energy was obtained for each catalyst by apparent optical thickness. The optimum concentration of photocatalyst Degussa P-25 was 0.2 g/l in 0.86 cm of thickness, and for photocatalyst Aldrich it was 0.3 g/l in 0.80 cm of thickness.